2006
DOI: 10.1002/app.23659
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polymerization of lactams: A comparative study on various methods of measuring the conversion of ε‐caprolactam to polyamide 6

Abstract: Anionic ring-opening polymerization of lactams leads to the formation of poly(lactams) or polyamides. This work aimed at comparing the performance of four methods for measuring the conversion of -caprolactam (CL) to polyamide 6. The latter was either a homopolymer (PA6) or grafts onto polystyrene (PS-g-PA6 graft copolymer). Those four methods were mass balance based on solvent extraction (methanol, water, THF, or acetone), mass balance based on vacuum drying at 140°C, thermogravimetric analysis (TGA), and elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
(43 reference statements)
2
30
0
Order By: Relevance
“…The PS‐ g ‐PA6 graft copolymers were obtained by the anionic polymerization of CL onto a random copolymer of styrene (St) and TMI in the presence of NaCL. Details on the polymerization principle, procedure, and the structural analysis methods of PS‐ g ‐PA6 can be found elsewhere [27–29]. Table 2 shows the selected characteristics of four PS‐ g ‐PA6 graft copolymers used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PS‐ g ‐PA6 graft copolymers were obtained by the anionic polymerization of CL onto a random copolymer of styrene (St) and TMI in the presence of NaCL. Details on the polymerization principle, procedure, and the structural analysis methods of PS‐ g ‐PA6 can be found elsewhere [27–29]. Table 2 shows the selected characteristics of four PS‐ g ‐PA6 graft copolymers used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…They found that substantial improvement in the elongation at break and ductility using the graft copolymer with PS segments with molecular weight as high as 66,000 g/mol and with a PS proportion equal to or higher than EVA. Our previous work reported on a novel method to synthesize a graft copolymer with a controlled structure by the activated anionic polymerization of ε‐caprolactam (CL) using sodium ε‐caprolactam (NaCL) as catalyst and 3‐isopropenyl‐α,α‐dimethylbenzene isocyanate (TMI) bearing polypropylene (PP) or PS as activator (PP‐ g ‐TMI or PS‐ co ‐TMI) [25–29]. The graft copolymer (PS‐ g ‐PA6) with PS as backbone and polyamide 6 (PA6) as grafts with different structures and compositions were used as compatibilizer for PS and PA6 blends [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…This makes PA6 one of the main engineering materials in use today. According to different reports [10][11][12][13][14][15][16][17], there are three main parameters that govern the polymerization of APCL: the catalyst (type and concentration), activator (type and concentration), and also the initial polymerization temperature. In almost all published studies, this process has been carried out in an inert atmosphere.…”
mentioning
confidence: 99%
“…Details on the synthesis and characterization procedures can be found in the literature (Zhang et al, 2006(Zhang et al, , 2007a(Zhang et al, , 2008a. Table 1 gathers selected characteristics of the PS-g-PA6.…”
Section: Synthesis and Characteristics Of Ps-g-pa6 Graft Copolymermentioning
confidence: 99%